PENGARUH PIJAT ABDOMEN TERHADAP KONSTIPASI PADA LANSIA PENGHUNI PANTI JOMPO - Zaenal Amirudin; Indar Widowati; Bios Cendekia Wigatiningtias (Jurnal Lintas Keperawatan, 2023)
Constipation is a symptom of difficulty defecating which is characterized by hard stool consistency, large size, and decreased frequency of defecation which is common in the elderly. Abdominal massage is an intervention that increases intra-abdominal pressure, which can stimulate defecation in the rectum. The aim of this research is to determine the effect of abdominal massage therapy as a solution to treat constipation in the elderly. Thirty elderly people with constipation and constipation problems were recruited using purposive sampling to undergo abdominal massage. pre-experiment one group pre-post test design was used to measure the level of constipation. The Wilcoxon Test results prove (Wcount = 40.05), meaning that abdominal massage can reduce constipation in the elderlyKeywords: Constipation, Abdominal Massage Therapy, Elderly